Design of a Tolaki Language Teaching Module to Enhance Cultural Literacy among Students at SD Negeri 2 Konda - Astri Wulandari; Waode Ekadayanti; Arna juwairiyah (CV. Gerasi Insan Nusantara, 2025)
This study aimed to identify development needs, design a Tolaki language teaching module, and assess its feasibility as an effort to enhance the cultural literacy of students at SD Negeri 2 Konda. The study employed Research and Development (R&D) using the ADDIE development model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants were teachers and students at SD Negeri 2 Konda. Data were collected through observation, interviews, documentation, tests, and validation by content, language, and media experts. Qualitative and quantitative analyses were used to determine development needs, the module-development process, and the feasibility of the resulting module. The findings showed that Tolaki language instruction at SD Negeri 2 Konda required a teaching resource containing basic Tolaki vocabulary, simple language structures, elements of local culture, learning activities, exercises, and evaluations tailored to the characteristics of elementary school students. Validation by content, language, and media experts indicated that the module was highly feasible for use in instruction. The implementation results also showed that the module increased students' active participation and enthusiasm and strengthened their understanding of the Tolaki language and local cultural values. The study concludes that the developed Tolaki language teaching module is feasible for use as a local-content teaching resource and has the potential to enhance elementary school students' cultural literacy.